Contribution Attribution As the Possible Next Step for “Crowdsourced” Engineering Design and Product Development - Mark J. Jakiela (Washington University Journal of Law & Policy, 2009)
This Article poses two questions: Can the crowdsourcing model be applied to engineering design and product development? If so, how?
Keywords: User-generated content; User-generated Internet content; Engineering design; Outsourcing; Product development; Crowdsourcing